Solvability of Nonlocal Fractional Boundary Value Problems - Zhongmin Huang; Chengmin Hou (Discrete Dynamics in Nature and Society)
This paper is devoted to introduce a new approach to investigate the existence of solutions for a three-point boundary value problem of fractional difference equations as fllows: , , and = We present an existence result at resonance case. The proof relies on coincidence degree theory.